Difficulties in emotion regulation and suicide ideation and attempt in adolescent inpatients. (January 2019) - Hatkevich, Claire; Penner, Francesca; Sharp, Carla
Highlights: Research lacks on ER difficulties and suicidal outcomes in psychiatric youth. Limited access to ER strategies was positively associated with suicide ideation. Impulse control difficulties were negatively associated with suicide ideation. Strategies, not impulse control, remained associated with SI in both sexes. Past year suicide ideation uniquely associated with lifetime suicide attempt. Abstract: This study aimed to examine the concurrent relation between six dimensions of emotion dysregulation, proposed by Gratz and Roemer (2004), and suicide ideation and attempt in a large sample of psychiatric adolescent inpatients. A sample of 547 adolescent inpatients completed measures on dimensions of emotion dysregulation, psychiatric diagnoses, and suicidal ideation and attempt. Binary logistic regression analyses revealed that limited access to emotion regulation strategies, difficulties in impulse control, and mood disorder diagnosis, were significantly associated with past year suicidal ideation, covarying for other emotion dysregulation subscales, anxiety and externalizing diagnoses, sex, and age. However, difficulties in impulse control was not significantly related to suicide ideation when analyses were conducted separately by sex. Binary logistic regressions also revealed that past year suicidal ideation uniquely and significantly associated with lifetime attempt, covarying for sociodemographics, psychiatric diagnoses, and all emotion dysregulation subscales; these results held when analyses were also conducted separately by sex. Results indicating an association between perceived limited emotion regulation strategies and suicide ideation are consistent with existing research and suicide-focused theory. This finding may have some tentative benefit to informing clinical assessment and treatment of suicidal thoughts. Other findings are discussed.